2019
DOI: 10.1130/g45950.1
|View full text |Cite
|
Sign up to set email alerts
|

Debris-flow volume quantile prediction from catchment morphometry

Abstract: Estimation of the volumes of potential future debris flows is a key factor in hazard assessment and mitigation. Worldwide, however, there are few catchments for which detailed volume-frequency information is available. We (1) reconstructed volume-frequency curves for 10 debris-flow catchments in Saline Valley, California (USA), from a large number of well-preserved, unmodified surficial flow deposits, and (2) assessed the correlations between lobe-volume quantiles and a set of morphometric catchment characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Locally, and in relatively homogenous geological, geomorphological and climatic locations, single watershed variable correlations with F–M pairs may be achieved (e.g. de Haas and Densmore, 2019), but this necessitates a statistically significant number of detailed studies.…”
Section: Introductionmentioning
confidence: 99%
“…Locally, and in relatively homogenous geological, geomorphological and climatic locations, single watershed variable correlations with F–M pairs may be achieved (e.g. de Haas and Densmore, 2019), but this necessitates a statistically significant number of detailed studies.…”
Section: Introductionmentioning
confidence: 99%
“…De Haas et al. (2019), in their study of unburned debris flow fans in Saline Valley, California, similarly found that debris‐flow volumes were best correlated with watershed morphometric parameters related to basin size (e.g., area, length, perimeter) rather than slope. In the burned portion of our study area, debris‐flow volume had a relatively strong, negative correlation with the Melton Ratio ( ρ = −0.74, p = 0.03), followed by a more modest positive correlation with basin area ( ρ = 0.64, p = 0.07).…”
Section: Discussionmentioning
confidence: 98%
“…The first four watershed characteristics ( A23 , F23 , S50 , RU ), which provide information about slope or the combination of steep slopes and drainage area, are similar to measures of terrain steepness that are often found to be related to debris‐flow likelihood (Cannon et al., 2010; Staley et al., 2017). The last five watershed characteristics ( A , R , L , P , MR ), which except for MR are generally related to watershed size, are more likely to be related to debris‐flow volume (Cannon et al., 2010; De Haas & Densmore, 2019; Gartner et al., 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations